The Organization of Irrational Beliefs in Academic Burnout - Rahman, Diniy Hidayatur; Hotifah, Yuliati; Simon, Irene Maya; Kuha, Ariya; Fathorrazi, A (Jurnal Kajian Bimbingan dan Konseling, 2024)
From the Rational-Emotive Behavior Therapy (REBT) perspective, irrational beliefs are posited as the primary catalysts for a myriad of problems, including academic burnout. This study aims to examine the theoretical model of irrational beliefs organization in academic burnout. The hypothesized model delineates the following pathways: (1) from demandingness (DEM) to academic burnout (BURN) via catastrophizing (CAT); (2) from demandingness (DEM) to academic burnout (BURN) via low frustration tolerance (LFT); and (3) from demandingness (DEM) to academic burnout (BURN) via self-depreciation (DEP). To achieve the aim, the study employed a causal relationship design. 424 subjects obtained by stratified random sampling participated in the study. The Indonesian version of the Attitude Belief Scale II and the School Burnout Inventory were used to collect data. Data analysis was carried out using path analysis with SPSS 16. The results show that the hypothesized model has received adequate empirical support after eliminating a path from LFT to BURN. In conclusion, two alternative paths of irrational beliefs contribute to academic burnout: (1) the path from DEM to BURN via CAT; and (2) the path from DEM to BURN via DEP. These results underscore demandingness as a primary irrational belief that affects academic burnout via two other secondary irrational beliefs: catastrophizing and self-depreciation. Conversely, low frustration tolerance does not emerge as a significant contributor to academic burnout within this framework.